DUKUNGAN KELUARGA DENGAN UPAYA MEMINIMALISIR SERANGAN STROKE PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS BONTONYELENG KECAMATAN GATTARENG - Aszrul AB; Andi Suswani (Jurnal Kesehatan Panrita Husada, 2017)
Family support is very important for stroke patients or those who experience a stroke. Family support is given to health care. Broadly speaking, health efforts are divided into three prevention, curative prevention and rehabilitation efforts (Maulana, 2014: 38). Successfully preventing stroke in patients with hypertension, the family must provide support for patients with hypertension so that lifestyle changes.The purpose of this study was to study the relationship between family support for efforts to prevent stroke in hypertensive patients in the Bontonyeleng Public Health Center Gantarang District, Bulukumba Regency.This study uses quantitative research design using descriptive design. The sample of this study amounted to 50 people taken by the total sampling method that is all participants who were used as the study sample. Data analysis in this study used the Chi Square test statistic test.Based on the results of the research obtained by the respondents, there were mostly in the good category as many as 29 respondents (58%), while the family efforts in minimizing stroke in hypertensive patients were mostly found in the non-done category as many as 33 respondents (66%). The results of the analysis using the Chi Square statistical test obtained a p value of 0,000, thus p <α (0,000 <0,05).The conclusion of this study is about the relationship between families with efforts to minimize stroke in hypertensive patients in the work area of ​​Bontonyeleng Public Health Center, Gantarang District, Bulukumba Regency.Suggestions from this study are to be able to add information and input for health workers to be able to increase assistance for hypertensive patients regarding family needs with family prevention in minimizing stroke in patients with hypertension.